2001
DOI: 10.1086/322332
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Mass Ejection of 2000 July 14 Flare Event: Imaging from Near‐Sun to Earth Environment

Abstract: We report the results of our investigation of interplanetary e †ects caused by the large solar Ñare (X5.7/ 3B) that occurred on 2000 July 14. In association with this event a bright, fast, halo coronal mass ejection (CME) was observed. The analysis of multiwavelength, high-cadence images obtained from the Radioheliograph shows the on-disk signatures of the initiation of the CME at low-coronal NancÓ ay heights, ¹2The formation of the CME inferred from the radio data indicates a nearly developed R _ . halo at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 24 publications
10
75
0
Order By: Relevance
“…The acceleration in the interplanetary medium of CMEs is well-established (Gopalswamy et al 2000(Gopalswamy et al , 2001Manoharan et al 2001;Manoharan 2006;Howard 2007). This acceleration has been explained by an increase of the ICME mass (snowplough model Tappin 2006) or due to Lorentz force (Chen 1996;Howard 2007), although it is more common to attribute this acceleration to drag forces (Vršnak 2001;Cargill 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration in the interplanetary medium of CMEs is well-established (Gopalswamy et al 2000(Gopalswamy et al , 2001Manoharan et al 2001;Manoharan 2006;Howard 2007). This acceleration has been explained by an increase of the ICME mass (snowplough model Tappin 2006) or due to Lorentz force (Chen 1996;Howard 2007), although it is more common to attribute this acceleration to drag forces (Vršnak 2001;Cargill 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Using scintillation data (IPS), Manoharan et al (2001) and Manoharan (2006) have found that ICMEs show a low decline in speed below 100 R (0.36 AU) and a rapid decrease after this distance. This behavior agree with the concavity of the curves in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…2 of Li et al [2001], Fig. 5 of Manoharan et al [2001], Figs. 3 and 8 of Yurchyshyn et al [2001], and Fig.…”
Section: Geometrical Interpretationmentioning
confidence: 98%
“…The radial profiles of some of the events indicate that the internal energy of the CME supports the propagation, i.e., the expansion (Manoharan et al, 2000;. Further, IPS data have been useful to quantify the force of interaction experienced by CMEs in the IP medium before their arrival at the near-Earth environment (Manoharan et al, 2001;Manoharan, 2006). In other words, the CMEs moving with speeds less than the background solar-wind speed are accelerated (or aided by the ambient wind).…”
Section: Interplanetary Scintillation Observationsmentioning
confidence: 99%
“…The propagation signatures of a CME in the space outside the LASCO field of view can be obtained from the remote-sensing Interplanetary Scintillation (IPS) technique (e.g., Manoharan et al 2001;Tokumaru et al 2005). The IPS method exploits the scattering of radiation from distant radio sources (quasars, galaxies, etc.)…”
Section: Interplanetary Scintillation Observationsmentioning
confidence: 99%